Amyloid-like assembly converting commercial proteins to water-insoluble adsorbents with ultrahigh adsorption capacity and excellent antifouling property for uranium extraction. Issue 6 (22nd December 2021) - Ye, Hao; Liu, Chang; Wu, Ming-Bang; Ma, Lu-Lin; Liu, Shi-Cheng; Zhong, Yu; Yao, Juming
Abstract : Uranium extraction from seawater is regarded as the most promising strategy for solving the concerns regarding the increasing demands of the nuclear industry. Abstract : Uranium extraction from seawater is regarded as the most promising strategy for solving the concerns regarding the increasing demands of the nuclear industry. Inspired by the functional proteins of natural biological entities like bacteria and proteins that can efficiently capture uranium, we have developed water-insoluble protein-based adsorbents via a one-step amyloid-like assembly process. This method could convert water-soluble commercial proteins like bovine serum albumin (BSA), lysozyme and ovalbumin into adsorbents via one-step methods, while maintaining plenty of adsorption sites on the outer surface. The results of molecular dynamics simulations confirm the strong binding affinity between uranium and oxygenic/nitrogen functional groups. The protein-based adsorbents can capture more than 1000 mg g −1 of uranium from ultralow concentration uranyl nitrate solutions (8 ppm) within 2 h. Both the adsorption capacity and adsorption rate are in the leading positions compared with those of other state-of-the-art adsorbents. Moreover, these adsorbents exhibit outstanding anti-fouling properties and recyclability. They could maintain more than 80% of their pristine performance even after ten cycles in a simulated marine environment. Furthermore, the adsorbents could be deposited on various porous substrates like sponges for dynamic adsorption, benefiting from the good adhesion property of the unfolded proteins. The modified sponges could adsorb 540.6 mg g −1 uranium from simulated seawater in 72 h, showing their great potential in the field of practical uranium extraction.